2018
DOI: 10.1038/s41419-018-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

High PGAM5 expression induces chemoresistance by enhancing Bcl-xL-mediated anti-apoptotic signaling and predicts poor prognosis in hepatocellular carcinoma patients

Abstract: Hepatocellular carcinoma (HCC) is the one of most common and deadly cancers, and is also highly resistant to conventional chemotherapy treatments. Mitochondrial phosphoglycerate mutase/protein phosphatase (PGAM5) regulates mitochondrial homeostasis and cell death, however, little is known about its roles in cancer. The aim of this study was to explore the clinical significance and potential biological functions of PGAM5 in hepatocellular carcinoma. For the first time, our results show that PGAM5 is significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…The expression of PGAM5 that dephosphorylates and activates ASK1 MAP3K [144] and prolongs survival of tumor cells in hepatocellular carcinoma (HCC) [145], and PLXNB2, an activator of the GTPase Rho [56], promoting ovarian cancer cell proliferation and invasion [57] and prostate tumor growth [58], as well as ICAM1, which activates Rho [54] and which increased metastasis in pancreatic ductal adenocarcinoma [55], were reduced (5- and 16-fold). On the other hand, the expression levels of SUSD2 (Figure 10A), a Notch 3-regulating protein that also suppresses metastasis in high-grade serous ovarian carcinoma [146], and of STAT6, playing a major role in regulation of IL-4 synthesis, reducing colon inflammation during tumorigenesis but facilitating tumor formation [147], increased (150- and 12-fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PGAM5 that dephosphorylates and activates ASK1 MAP3K [144] and prolongs survival of tumor cells in hepatocellular carcinoma (HCC) [145], and PLXNB2, an activator of the GTPase Rho [56], promoting ovarian cancer cell proliferation and invasion [57] and prostate tumor growth [58], as well as ICAM1, which activates Rho [54] and which increased metastasis in pancreatic ductal adenocarcinoma [55], were reduced (5- and 16-fold). On the other hand, the expression levels of SUSD2 (Figure 10A), a Notch 3-regulating protein that also suppresses metastasis in high-grade serous ovarian carcinoma [146], and of STAT6, playing a major role in regulation of IL-4 synthesis, reducing colon inflammation during tumorigenesis but facilitating tumor formation [147], increased (150- and 12-fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
“… 114 PGAM5 is a mitochondrial serine/threonine phosphatase that is upregulated in HCC tissue. 121 PGAM5 interacts with anti-apoptotic protein Bcl-XL, thereby preventing its degradation and inhibiting apoptosis. 121 Additionally, increased MCUR1 expression was associated with increased expression of anti-apoptotic protein Bcl-2.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Resistance to apoptosis also plays a role in the chemoresistance mechanisms of liver cancer cells. For example, an increased expression of mitochondrial phosphoglycerate mutase/protein phosphatase in liver cancer cells enhances chemoresistance to 5-fluorouracil by increasing the stability of Bcl-XL, and inhibiting the expression of Bax and cytochrome c, which eventually inhibit the apoptotic signaling pathway ( 29 ). A study suggested that HCC can resist apoptosis by overexpressing mitochondrial uncoupling protein to decrease mitochondrial membranes permeability ( 30 ).…”
Section: Mitochondria Regulate the Progression And Death Of Hepatocellular Carcinomamentioning
confidence: 99%